Migrações e identidades : várias óticas e perspectivas (SCIELO Books, 2017)
This book is the result of the I International Seminar on Migration and Identity, held in Salvador/BA. Each article presents a perspective around the themes of migrations and identities, whether from the perspective of human rights, gender or the posture of the State. The work aims to socialize the discussion in different public and private spheres.